Triterpenes and triterpene-glycoside from the leaves of Lawsonia inermis. - Binh, Nguyen Thi; Ky, Pham Thanh; Thao, Nguyen Phuong; Minh, Chau Van; Cuong, Nguyen Xuan; Kiem, Phan Van (Vietnam Journal of Chemistry, 2014)
From the leaves of Lawsonia inermis (syn. L. alba), two triterpenes augustic acid (1) and 1b,2a,3a,19a-tetrahydroxy-12-ursen-28-oic acid (2), and a triterpene-glycoside suavissimoside R1 (3) were isolated by using various chromatoghraphies. Their structures were characterized on the basis of the spectroscopic data (1D-NMR, HSQC, HMBC, ESI-MS) in comparison with the literature. This is the first report of 1 - 3 from Lawsonia species. Keywords: Lawsonia inermis, Lythraceae, Triterpene.